2019
DOI: 10.3390/nu11040792
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients Deficiencies in 374 Severely Malnourished Anorexia Nervosa Inpatients

Abstract: Introduction: Anorexia nervosa (AN) is a complex psychiatric disorder, which can lead to specific somatic complications. Undernutrition is a major diagnostic criteria of AN and it can be associated with several micronutrients deficiencies. Objectives: This study aimed to determinate the prevalence of micronutrients deficiencies and to compare the differences between the two subtypes of AN (restricting type (AN-R) and binge-eating/purging type (AN-BP)). Methods: We report a large retrospective, monocentric stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 47 publications
(55 reference statements)
2
40
0
4
Order By: Relevance
“…2 Owing to their fear of weight gain or becoming fat, patients severely restrict their diet and develop malnutrition to various degrees. 3 The Diagnostic Manual of Mental Disorders (DSM-V) has aligned the severity categories of anorexia nervosa to the WHO malnutrition categories. 4 With malnutrition, there are widespread endocrine abnormalities: stress hormones increase and sexual hormones reduce.…”
mentioning
confidence: 99%
“…2 Owing to their fear of weight gain or becoming fat, patients severely restrict their diet and develop malnutrition to various degrees. 3 The Diagnostic Manual of Mental Disorders (DSM-V) has aligned the severity categories of anorexia nervosa to the WHO malnutrition categories. 4 With malnutrition, there are widespread endocrine abnormalities: stress hormones increase and sexual hormones reduce.…”
mentioning
confidence: 99%
“…In a systematic review by Hanachi et al including 374 patients with AN (restricting (AN-R) and binge-eating/purging (AN-BP) type), it was found that zinc deficiency had the highest prevalence (64.3%), followed by vitamin D (54.2%), copper (37.1%), selenium (20.5%), vitamin B1 (15%), vitamin B12 (4.7%), and vitamin B9 (8.9%). The AN-BP subgroup had lower selenium ( p < 0.001) and vitamin B12 plasma concentration ( p < 0.036), whereas lower copper plasma concentration was observed in patients with AN-R type ( p < 0.022) [14].…”
Section: Resultsmentioning
confidence: 99%
“…Critical micronutrient deficiencies occur more often with longer illness duration. Zinc (64%) and vitamin D (54%) deficiencies are common while other vitamin deficiencies are less frequent [38][39][40][41][42].…”
Section: Anorexia Nervosa (An): Energy Macronutrient and Micronutriementioning
confidence: 99%